Contracting account audit on social networks - Jakovljević Nemanja; Jakovljević Stefan (Trendovi u Poslovanju)
Social network account audit is an independent review of social network activities to express a professional opinion on the fulfillment of objectives, business compliance, and information security of orders on social networks. It is in principle a voluntary activity and is not subject to legal obligation like some other types of audit such as the audit of financial statements. However, this does not diminish its fundamental importance, which is reflected in the fact that in situations where the other party is entrusted with the management of accounts on social networks, there is a gap in expectations that should be mitigated by performing a professional and independent review that will result in an objective and professional opinion. Therefore, the issue of contracting the social network account audit is exciting, especially given the sensitivity of the data being audited and the specific status of the parameters for logging into the account whose disposal must be subjected to strict treatment to ensure the safety of account holders. The subject of this paper is the analysis of aspects of contracting the audit of orders on social networks through the analysis of contracting parties and elements of the subject of contracting. The paper's main conclusion is that auditing is a sensitive topic that should be given additional attention and focus during preliminary social network account audit activities.